Establishment of cholangiocarcinoma cell lines from patients in the endemic area of liver fluke infection in Thailand - Sunitta Saensa-ard; Saman Leuangwattanawanit; Laddawan Senggunprai; Nisana Namwat; Sarinya Kongpetch; Yaovalux Chamgramol; Watcharin Loilome; Walaiporn Khansaard; Apinya Jusakul; Auemduan Prawan; Chawalit Pairojkul; Narong Khantikeo; et al. (Tumor Biology)
Cholangiocarcinoma is a rare type of cancer which is an increasingly discernible health threat. The disease is usually very difficult in diagnosis and various treatment modalities are typically not effective. Cholangiocarcinoma is a complex and very heterogeneous malignancy characterized by tumor location, different risk factors, molecular profiling, and prognosis. Cancer cell lines represent an important tool for investigation in various aspects of tumor biology and molecular therapeutics. We established two cell lines, KKU-452 and KKU-023, which were derived from patients residing in the endemic area of liver fluke infection in Thailand. Both of tumor tissues have gross pathology of perihilar and intrahepatic mass-forming cholangiocarcinoma. Two cell lines were characterized for their biological, molecular and genetic properties. KKU-452 and KKU-023 cells are both adherent cells with epithelium morphology, but have some differences in their growth pattern (a doubling time of 17.9 vs 34.8 h, respectively) and the expression of epithelial bile duct markers, CK7 and CK19. Cytogenetic analysis of KKU-452 and KKU-023 cells revealed their highly complex karyotypes; hypertriploid and hypotetraploid, respectively, with multiple chromosomal aberrations. Both cell lines showed mutations in p53 but not in KRAS. KKU-452 showed a very rapid migration and invasion properties in concert with low expression of E-cadherin and high expression of N-cadherin, whereas KKU-023 showed opposite characters. KKU-023, but not KKU-452, showed in vivo tumorigenicity in xenografted nude mice. Those two established cholangiocarcinoma cell lines with unique characters may be valuable for better understanding the process of carcinogenesis and developing new therapeutics for the patients